IMPLEMENTASI DESAIN 4 D DALAM KONSELING KELOMPOK DENGAN TEKNIK BIBLIOKONSELING UNTUK MENINGKATKAN LIERASI SAINS SISWA - Astuti, Indri; Mulyati, Iis (Jurnal Teknologi Pendidikan (JTP), 2024)
Abstract: The general aim of the research is to produce 4D design collaboration and group counseling using bibliocounseling techniques and to increase students' scientific literacy. The specific objectives of the research are to describe students' initial scientific literacy abilities, produce a 4D collaborative conceptual design model with group counseling using biblio-counseling techniques to increase scientific literacy and find out students' responses regarding the conceptual design of group counseling to increase scientific literacy using biblio-counseling techniques. Data collection methods through scientific literacy questionnaire instruments for students, expert validator questionnaires and student responses; interviews with guidance and counseling teachers and homeroom teachers, RPL documentation. The research respondents were 106 students who filled out the scientific literacy questionnaire, 65 students were involved in the development, three validators, one guidance and counseling teacher and the homeroom teacher. The research results showed that students' scientific literacy was generally less (35.20%) than 106 students. The results indicated five aspects of science literacy: (1) the role of science (32.78%/ 35 people) was not good; (2) scientific thinking and action 41.04% is quite good. (3) Science and Society 17.69% very less; (4) science media literacy 44.58% quite good, (5) Mathematics and science 41.51% quite good. Bibliocounseling techniques to increase scientific literacy in the form of aspirational story reading materials according to student problems. Design validation results (4.25) are good; material expert (3.85) good; media expert (3.95) is good. This means that in theory it is valid/suitable for use by student users. The results of empirical trials with individual groups of 3 people, small groups of 6 people and large groups of 26 people, group counseling using bibliocounseling techniques makes it easier and aspirational for students to increase scientific literacy. The results of 90% of students responding with 30 respondents were very good. This finding suggests that 4D collaboration and biblio-counseling technical group counseling aspire to increase scientific literacy. Key words: 4D model, scientific literacy, group counseling, bibliocounseling Abstrak: Tujuan umum penelitian untuk menghasilkan kolaborasi desain 4D dan konseling kelompok dengan teknik bibliokonseling dan untuk meningkatkan literasi sains siswa. Tujuan khusus penelitian yaitu, mendiskripsikan  kemampuan awal literasi sains siswa, menghasilkan model desain konseptual kolaborasi 4D dengan konseling kelompok dengan teknik bibliokonseling meningkatkan literasi sains dan mengetahui respon siswa tentang desain konseptual konseling kelompok untuk meningkatkan literasi sains dengan teknik bibliokonseling.   Metode pengumpulan data melalui Instrumen angket literasi sains untuk siswa, angket validator ahli dan respon siswa; wawancara dengan guru BK dan wali kelas, dokumentasi RPL. Responden penelitian 106 siswa mengisi angket literasi sains, 65 siswa terlibat dalam pengembangan, tiga validator, satu guru BK dan walikelas. Hasil penelitian menunjukkan literasi sains siswa secara umum kurang (35,20 %) dari 106 siswa. Hasil ditandai lima aspek lierasi sains: (1) peran sains (32,78 %/ 35 orang) kurang baik; (2) pemikiran dan tindakan ilmiah 41.04% cukup baik. (3)  Sains dan Masyarakat 17,69% kurang sekali; (4) literasi media sains 44,58% cukup baik, (5) Matematika dan sains 41,51% cukup baik. Bibliokonseling teknik untuk meningkatkan lierasi sains dalam bentuk bahan bacaan cerita aspiratif sesuai masalah siswa. Hasil validasi desain (4,25) baik; ahli materi (3,85) baik; ahli media (3,95) baik. Artinya secara teori valid/layak digunakan oleh pengguna siswa.  Hasil uji coba empiris dengan kelompok perorangan 3 orang, kelompok kecil 6 orang dan kelompok besar 26 orang, maka konseling kelompok dengan teknik bibliokonseling mempermudah dan mengaspirasi siswa untuk meningkatkan lierasi sains. Respon siswa dengan responden 30 orang diperoleh hasil 90 % memberikan   respon    baik sekali, temuan ini mengisyaratkan kolaborasi 4D dan konseling kelompok teknik bibliokonseling mengaspirasi meningkatkan literasi sains. Kata kunci: model 4D, literasi sains, konseling kelompok, bibliokonseling